Harnessing the epic electronic medical record to track indwelling ureteral stents in a pediatric population. Issue 1 (February 2022) - Wagner, Kathryn; Pingle, Srinath-Reddi; Walker, Kathryn; Floridia, Erin; Medina, Carlos; Rowe, Courtney K.
Summary: Introduction: Retention of indwelling ureteral stents due to loss to follow-up can result in significant harm to patients, often requiring multiple trips to the operating room. Despite widespread use of electronic medical records, there are few standardized options for urologists to track ureteral stents and no data on the rate of retained stents in a pediatric population. Objective: This pilot quality improvement project aims to: 1) develop a simple process to track indwelling ureteral stents using the Epic electronic medical record and 2) determine the incidence of forgotten stents in a pediatric population. Methods: We identified that operating room staff scan a barcode for ureteral stents at the time of surgery to log the stent as "Implanted" in the patient's medical record. The stent can later be marked as "Explanted" at the time of removal. A report was designed within Epic to identify all patients with a ureteral stent implanted from April 2014 to June 2019 at our hospital. We reviewed the records of patients whose stents had never been marked as "Explanted" to determine if any had a retained stent. A workflow was then designed to ensure staff would mark stents as "Explanted" at the time of removal and to periodically run the report within Epic to ensure that all patients with ureteral stents in place have appropriate follow-up. Results: Our report identified 152 ureteral stents with a status of "Implanted". 3 patients did not have evidence of stent removal documented in their medical record. Follow up with these patients revealed stent removal at an outside location. Discussion: Current approaches to stent tracking are laborious with limitations to adherence. The Epic software directly incorporates stent tracking into the individual patient chart allowing for easy implementation and follow up. Our study revealed no retained stents in our pediatric population. Conclusions: All patients with ureteral stents placed at a single institution over a 5-year period were easily identified using an automated Epic report. Through this report, we will prevent morbidity associated with stent retention. This technique could easily be implemented at other hospital systems that use Epic, and similar reporting tools could be designed within other electronic medical record systems. The incidence of ureteral stent retention in the pediatric population is likely significantly lower than for their adult counterparts. Summary Figure Algorithm for tracking ureteral stent placement and removal at our institution. Fig